Pengaruh Keputusan Nasabah untuk Menggunakan Fasilitas Mobile Banking dalam Standar Pelayanan di PT. Bank BRI Syariah Cabang Pekanbaru - Rahmawati, Rahmawati; Idola, Noer Ariska (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2018)
In modern times, everything is tackled fast and precisely due to the rapid development of technology and development in all fields. This is because human needs for information are increasingly complex and it demands us to be more optimal in accessing all information through technology facilities. In this study, the writers are interested in raising the title Influence of Customer Decisions to Use Mobile Banking Facilities in service standards at PT. Bank BRI Syariah Branch Pekanbaru city. The object of this research was conducted at PT. Bank BRI Syariah Branch Pekanbaru which is located at Jalan Arifin Ahmad No.7-9 in Pekanbaru city. The sampling technique used was the Nonprobability Sampling method with respondents' search procedure techniques based on Accidental Sampling, in which the sample in this study were 67 respondents. The data analysis technique used is quantitative with multiple linear regression method SPSS 16. The results of data processing from the regression equation are Y = 4,297 + 0,635 X1 + 0, O56 X2 + 0,269 X3 + -0,159 X4. Furthermore, from the results of the t-test, the variables that most influence the customer's decision in using mobile bankingis cultural factors proven from the t-count> t-table of 4.438> 1.996, social factors of 0.586 <1.996, personal factors of 2.015> 1.996 and psychological factors of -1.170 <1.996 . While the test F-count> F-table proved to be 5.887> 2.51 with a significant value of 0.000 <0.05 which means that H0 is rejected and H1 is accepted. While the test results of the coefficient of determination show the percentage of variables of cultural factors, social factors, personal factors and psychological factors on customer decisions of 0.275 (27.5%) and the remaining 72.5% are explained by other variables outside the regression model. The conclusion is that the variables of cultural factors, social factors, personal factors and psychological factors simultaneously influence the customer's decision. The factors affecting the customer's decision to use mobile banking facility at PT. BRI Syariah branch Pekanbaru  is generally in accordance with the established rules and service standards in the world of Islamic Banking.